Answer:
I solved the question 1 to 14 but I'm sorry I cannot do 15 -20
Step-by-step explanation:
hope this helps
Answer:
28
Length=2(x-1)
Width=5
Area=length*width = (2(x-1))(5) = (2x-2)(5) = 10x-10
29
His reasoning is illogical because whether or not an expression has a term that is being subtracted isn't relevant; technically there are an infinite amount of ways to represent a value. Plus you can just compute the expressions and see that they're equal:
6x-2x+4 = 4x+4
4(x-1) = 4x+4
30
The two expressions are equal because when you compute the expression 4(n+3)-(3+n) , you get 3n+9:
4(n+3)-(3+n) = 4n+12-3-n = 3n+9
31
The two expressions are equal because when you compute the expression 2(2n-1), you get 4n-2.
2(2n-1) = (2)(2n)+(2)(-1)=4n-2
32
5(g+14)=(5)(g)+(5)(14)=5g+70
The expressions aren't equal as 5(g+14) equates to 5g+70 and 5g+70≠5g+14.
Answer:
Step-by-step explanation:
It continues to go up in the positive X and Y Axis. Like an exponential function
Answer: sorry my g i need the points lol
Step-by-step explanation: yes
They are both in the thousands category